Where Revelation is Silent: Shari’a, Reason, and Islamic Natural Law - Emon, Anver M. ca. 20./21. Jh. (Bulletin for the study of religion, 2010)
My general line of research concerns the relationship between reason and authority in Shari’a. In particular, I am currently completing a book on Islamic natural law theories, in which I provide an analysis of how premodern Muslim jurists theorized about the authority of reason as a source of Shari’a norms where source-texts (e.g. Qur’an and Sunna) are otherwise silent.